A case series to investigate food‐related fear learning and extinction using in vivo food exposure in anorexia nervosa: A clinical application of the inhibitory learning framework. (10th September 2018) - Cardi, Valentina; Leppanen, Jenni; Mataix‐Cols, David; Campbell, Iain C.; Treasure, Janet
Abstract: Objective: Anorexia nervosa is characterized by severe malnutrition. This study tested the hypothesis that fear of food is a learned behaviour and evaluated the feasibility and effectiveness of gradual exposure to food to improve eating behaviour in people with anorexia nervosa. Methods: Eighteen women were recruited and completed baseline self‐reports. They were interviewed regarding early experiences of eating and the development of food‐related anxiety. Participants received eight sessions of in vivo food exposure. Results: Findings indicated that fear of food is a learned behaviour, associated with catastrophic thoughts around the consequences of eating and safety behaviours. Patients consumed at least half of the food item selected in all but one session. Body mass index increased, and food restriction, eating concern, eating disorder‐related preoccupations, and overall anxiety reduced (medium/large ES). Conclusion: Findings corroborate an anxiety‐based model of anorexia nervosa and support the relevance of targeting food‐related fears using exposure‐based protocols.